2004
DOI: 10.1179/027249304225019082
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of kangaroo mother care and conventional incubator care for thermal regulation of infants < 2000 g in Nigeria using continuous ambulatory temperature monitoring

Abstract: Although skin-to-skin contact (or kangaroo mother care, KMC) for preterm infants is a practical alternative to incubator care, no studies have compared these methods using continuous ambulatory temperature monitoring. To compare thermal regulation in low birthweight infants (< 2000 g) managed by KMC alternating with conventional care (CC) and to determine the acceptability to mothers of KMC, an experimental study with a crossover design with observational and qualitative data collected on temperature patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 20 publications
1
47
1
3
Order By: Relevance
“…Various interventions for prevention and management of hypothermia have been tested in community as well as hospital settings, and have added to the existing evidence base. 3,5,8,[89][90][91][92][93][94] Warm chain The 'warm chain' 32 is a set of 10 interlinked procedures to be taken at birth and during the following few hours and days to prevent hypothermia by minimizing heat loss in all newborns. Failure to implement any one of these procedures will break the chain and put the newborn baby at risk of hypothermia.…”
Section: Recognition Of Hypothermia Measurement and Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various interventions for prevention and management of hypothermia have been tested in community as well as hospital settings, and have added to the existing evidence base. 3,5,8,[89][90][91][92][93][94] Warm chain The 'warm chain' 32 is a set of 10 interlinked procedures to be taken at birth and during the following few hours and days to prevent hypothermia by minimizing heat loss in all newborns. Failure to implement any one of these procedures will break the chain and put the newborn baby at risk of hypothermia.…”
Section: Recognition Of Hypothermia Measurement and Detectionmentioning
confidence: 99%
“…97 The practice of Kangaroo Mother Care in hospitalized LBW infants has been associated with a number of benefits, and is now considered to be at least as good as standard care with incubators. 89,91 Besides improved thermoregulation of the newborn, other potential benefits include improved maternal-infant bonding, more rapid transition to physiological stability following birth, reduced crying and longer periods of alertness, improved breastfeeding and growth, reduced incidence of serious bacterial infections and earlier discharge from hospital. 5 STSC was shown to be at least as effective as incubator care for the management of hypothermia in normal birth weight neonates in hospital settings.…”
Section: Recognition Of Hypothermia Measurement and Detectionmentioning
confidence: 99%
“…The technique has found widespread acceptance for care of medically stable, hospitalized LBW infants weighing <2000 g. [2][3][4][5][6][7][8] The practice of KMC in hospitalized LBW infants has been associated with a number of benefits, and is now considered to be at least as good as standard care with incubators. 2 Potential benefits include improved maternal-infant bonding, more rapid transition to physiological stability following birth, reduced crying and longer periods of alertness, improved breastfeeding and growth, reduced incidence of hypothermia and serious bacterial infections, and earlier discharge from hospital.…”
Section: Introductionmentioning
confidence: 99%
“…A Nigerian experimental study on thermal regulations of infants weighing less than 2000 grams found that the risk of hypothermia was 90% reduced when baby is nursed in KMC compared to conventional care (Ibe et al, 2004).…”
Section: Thermal Controlmentioning
confidence: 99%